Increasing sika deer population density may change resource use by larval dung beetles - Yama, Hayato; Naganuma, Tomoko; Tochigi, Kahoko; Trentin, Bruna Elisa [UNESP]; Nakashita, Rumiko; Inagaki, Akino; Koike, Shinsuke (Public Library of Science (PLoS), 2019)
Because animal feces contain organic matter and plant seeds, dung beetles (Scarabaeinae) are important for the circulation of materials and secondary seed dispersal through burying feces. Dung beetles are usually generalists and use the feces of various mammals. Additionally, the larval stages have access to feces from only one mammal species leaving them susceptible to changes in animal fauna and variations in animal populations. Here, we explain the effects of resource availability changes associated with sika deer (Cervus nippon) overabundance on dung beetle larvae feeding habits in Japan. δ15N values were notably higher in raccoon dog and badger dung than in that of other mammals. A dung beetle breeding experiment revealed that the δ15N values of dung beetle exoskeletons that had fed on deer feces during their larval stage were significantly lower than those of beetles that had fed on raccoon dog feces. The δ15N values of the adult exoskeleton were significantly lower in a deer high-density area than in a low-density area in large dung beetles only. It is possible that the high-quality feces, such as those of omnivores, preferred by the large beetles decrease in availability with an increase in deer dung; large beetles may therefore be unable to obtain sufficient high-quality feces and resort to using large amounts of low-quality deer feces. Small dung beetles may use the easily obtained feces that is in high abundance and they may also use deer feces more frequently with increases in deer density. These findings suggest that a larval resource shift associated with deer overabundance may affect ecosystem functions such as soil nutrient cycling and seed dispersal.